(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Research focus and aim: To investigate the usability and utility of the SnipTouch innovative agility training device prototype in patients with upper extremity impairments after stroke. Research methods used: The study of several case studies was selected by formulating the research phenomenon and proposing two units of analysis- 1) usability and 2) utility of innovative prototype device SnipTouch. The multiple case study involved 7 stroke survivors with impaired upper limb functions who participated in eight physiotherapy sessions adding the SnipTouch intervention. The device operates on a dexterity training principle, where the main task is to quickly touch a lit button. Participants underwent pre-intervention upper extremity assessments using ROM, MMT, NRS, MAS, FMA-UE, 9HPT, BBT, and RTT. After the eighth session of physical therapy, reassessments were conducted with the same tools, supplemented by semi-structured interviews and usability evaluations using UEQ and SUS. The collected data were compiled and analysed using established data analysis methods. Results: Five participants assessed the usability of the equipment in the SUS questionnaire as outstanding (from 87,5 to 97,5 points), one participant as excellent (82,5 points) and one very good (77,5 points). The UEQ on six scales resulted in the following device evaluation: attractiveness 2.6, perspicuity 2.79, efficiency 2.32, dependability 2.14, stimulation 2.64, novelty 2.43. The UEQ benchmark classifies the innovative prototype device SnipTouch into Excellent category. The results of the upper limb functional tests show improvements in all participants. The main Conclusions and Recommendations: The results of the study demonstrate that the SnipTouch innovative device prototype is usable and the overlap of qualitative and quantitative data confirmed the utility of the device in improving reaction time, range of motion, agility, movement coordination, muscle strength, in addition to conventional rehabilitation therapy methods for stroke patients.